PERAN LEMBAGA KEUANGAN SYARIAH DALAM UPAYA MENINGKATKAN TARAF HIDUP MASYARAKAT DI INDONESIA - Imroatus Sholiha (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2025)
This article examines the role of Islamic financial institutions in efforts to improve people's standard of living. This study uses library research, which is a research method using several libraries such as journal articles, books, documents and so on. The research was conducted in depth by looking for research ideas then determining the focus to be raised, collecting appropriate reading materials, reviewing reading materials in depth and looking for additional information then starting to write a report. The results of the study indicate that Islamic financial institutions have a role in efforts to improve people's standard of living. The roles and efforts made are by providing sharia-based business financing to the community, so that it can create economic independence for the community. Then the second is optimizing the management of zakat, infaq, alms and waqf. The third is increasing financial access or financial inclusion for all levels of society so that there is equitable prosperity.